2009
DOI: 10.1080/10408390902841529
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design Principles for Delivery of Bioactive Components in Nutraceuticals and Functional Foods

Abstract: There have been major advances in the design and fabrication of structured delivery systems for the encapsulation of nutraceutical and functional food components. A wide variety of delivery systems is now available, each with its own advantages and disadvantages for particular applications. This review begins by discussing some of the major nutraceutical and functional food components that need to be delivered and highlights the main limitations to their current utilization within the food industry. It then di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
419
0
12

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 841 publications
(435 citation statements)
references
References 160 publications
4
419
0
12
Order By: Relevance
“…Over recent decades, some researchers have investigated the application of encapsulation for functional food components and drugs in the suitable edible delivery system McClements et al, 2009;deVos et al, 2010;Tavares et al, 2014). A large diversity of food proteins (for example whey protein, casein, gelatin, wheat gluten, and myosin) is accessible as building blocks in the formation of delivery systems (McClements et al, 2009).…”
Section: Physical and Mechanical Properties Of Protein Based Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over recent decades, some researchers have investigated the application of encapsulation for functional food components and drugs in the suitable edible delivery system McClements et al, 2009;deVos et al, 2010;Tavares et al, 2014). A large diversity of food proteins (for example whey protein, casein, gelatin, wheat gluten, and myosin) is accessible as building blocks in the formation of delivery systems (McClements et al, 2009).…”
Section: Physical and Mechanical Properties Of Protein Based Filmsmentioning
confidence: 99%
“…A large diversity of food proteins (for example whey protein, casein, gelatin, wheat gluten, and myosin) is accessible as building blocks in the formation of delivery systems (McClements et al, 2009). Previous studies indicate that the biocompatibility and release capability of proteins are closely related to their molecular properties, including structural properties, conformational characteristics, and thermal stability (Mitragotri et al, 2014;McClements et al, 2009). As discussed before, some studies have demonstrated that ACP exposure can selectively alter the protein conformation and function, depending on biological origin, plasma type, and treatment condition.…”
Section: Physical and Mechanical Properties Of Protein Based Filmsmentioning
confidence: 99%
“…This characteristic allows use of these structures as drugdelivery vehicles for controlling the release of incorporated agents. The lipid molecules in foods may be organized into a number of different forms, including as bulk, structural, emulsified, colloidal, or interfacial structures (McClements, 2005). However, invariably, all ingested lipids ends up as an emulsion either by gastric emulsification or prior to ingestion during manufacturing process.…”
Section: Lipidsmentioning
confidence: 99%
“…Nevertheless, the structural design of these systems is still very far from an exact science due to their compositional and structural complexity. Further research is still needed to achieve a detailed understanding of the molecular characteristics, structural organization, physicochemical properties, and functional performance of these delivery systems (McClements et al, 2009). …”
Section: Lipid Matricesmentioning
confidence: 99%
“…Moreover, blood is a rich source of iron and proteins of high nutrition and functional quality [10]. Meats have great potential for delivering important nutrients such as antioxidants, minerals, dietary fiber fatty acids, and bioactive peptides into the diet [11,12]. However, to manufacture prosperous and quality products with these constituents, advanced technology's necessity be fully developed to significant.…”
Section: Introductionmentioning
confidence: 99%